In vitro, ex vivo and in vivo studies on anti-hypertensive-loaded transdermal and buccal patches - Biswas Majee, Sutapa; Gupti, Souvik; Mishra, Trisha; Bera , Rachayeeta (Journal of Drug Delivery and Therapeutics, 2025)
The occurrence of hypertension is increasing slowly among urban and rural segments of the Indian population, irrespective of gender. It can affect quality of life and also lead to mortality under serious circumstances. Although several oral anti-hypertensive medications are available in the Indian market, the management of hypertension is reported to be poor. Anti-hypertensive–based transdermal or buccal patches may be necessary for patients where oral or parental route of administration is not possible or when no better control is achievable. Apart from Catapres®TTS, no other transdermal or buccal film of anti-hypertensive could be identified in the global market to date. However, the literature survey of published research articles since 2004 in the specialized databases of Elsevier, PubMed, and Cambridge using the keywords such as “anti-hypertensive”, “buccal”, and “transdermal” reveals more than 30 studies on fabrication, in vitro, and ex vivo characterization of transdermal and buccal films of anti-hypertensive agents. Among these, only 10 articles presented in vivo studies in animal models with no studies on human volunteers. Few reported stability studies as per ICH guidelines and skin irritation studies.  The present review article aims to reflect on the polymers, plasticizers, and penetration enhancers employed, outcomes of different studies on drug release, diffusion, and permeation, identify limitations and weaknesses of the reported studies, emphasize future research directions, and establish the potential reasons for not finding another successful anti-hypertensive loaded transdermal or buccal patch being launched.Keywords: Anti-hypertensive, buccal, ex vivo permeation, in vitro drug release, in vivo studies, transdermal